Comparison of Item Parameters of WAEC, NECO and NABTEB Mathematics Multiple Choice Questions Obtained Using IRT in Anambra State - Hassan Muhammad (Darul Yasin Al Sys, 2026)
Nigeria’s senior school certificate examinations are administered by the West African Examinations Council (WAEC), National Examinations Council (NECO), and National Business and Technical Examinations Board (NABTEB); however, the psychometric comparability of their Mathematics items requires systematic evaluation. This study compared the mean difficulty, discrimination, and guessing parameters of the Mathematics multiple-choice items administered by the three examination bodies in 2022 and 2023. A descriptive survey design was employed, guided by six research questions and six corresponding hypotheses. The population comprised 57,150 Senior Secondary 3 students from public secondary schools, with reported registrations of 57,150 for WAEC, 44,853 for NECO, and 2,250 for NABTEB. A sample of 1,600 students was selected through a multistage sampling procedure. The instruments consisted of the 2022 and 2023 Mathematics multiple-choice examination items developed by WAEC, NECO, and NABTEB, which were administered by trained research assistants who were Mathematics teachers in the sampled schools. Responses were subjected to item analysis within an item response theory framework using Mplus Version 7.4. Mean parameter estimates were calculated to answer the research questions, while one-way analysis of variance was conducted at the .05 significance level to test the hypotheses. For both years, NABTEB items had the highest mean difficulty parameters, followed by WAEC and NECO. In 2022, NABTEB items had the highest mean discrimination parameter, followed by WAEC and NECO; in 2023, WAEC ranked highest, followed by NABTEB and NECO. For the guessing parameter, NABTEB ranked highest in 2022, followed by NECO and WAEC, whereas NECO ranked highest in 2023, followed by NABTEB and WAEC. Statistically significant differences were found among the examination bodies in the mean difficulty, discrimination, and guessing parameters during the period examined. These findings demonstrate variation in the psychometric characteristics of the three examinations and underscore the need for WAEC, NECO, and NABTEB to strengthen their item-analysis and test-development procedures.